ANALYSIS OF REGIONAL DISPARITIES INI SOCIO-ECONOMIC ASPECTS IN SOUTHEAST SULAWESI PROVINCE - Ode, Muhamad Fadli; Rianda, La; Balaka, Muhammad Yani; Taridalla, Sabrilah; Padar, Sekar Alim; Hiromi, Rahma; Rahmatika, Sinta; Fajar, Nur Ahya (USN Kolaka, 2024)
This research aims to analyze the level of regional disparity using the Williamsom Index analysis, as well as to analyze the socio-economic aspect experiencing that disparity by examining economic development and human resource development. The research results indicate the presence of regional disparity in Southeast Sulawesi Province. The results of the Williamson Index measurement show that Southeast Sulawesi still has a high level of disparity and has experienced fluctuations over the past the years. The highest level of disparity occurred in 2012 at 0,71 (almost perfect disparity) and the lowest in 2019 at 0,44 (moderate disparity). It experienced fluctuations with an increase in disparity peaking in 2013 at 0.67.(disparitas sangat tinggi). The Gini Index measurement also indicated a gap in 2010 of 0.59, categorized as highly unequal. Regional disparities in Southeast Sulawesi Province occur due to differences in regional resource potential and management. The region's inability to pursue development acceleration has resulted in continued isolation, leading to persistent economic capability differences that impact other developments, primarily in road infrastructure, human resource development, and regional progress.